2022
DOI: 10.1177/14644207221118686
|View full text |Cite
|
Sign up to set email alerts
|

Processing and performance evaluation of agro wastes reinforced bio-based epoxy hybrid composites

Abstract: Agro-wastes have a huge potential to be utilized as lignocellulosic reinforcements in polymer composites. This will not only play an important role in waste management but will also strengthen sustainable production. In the present work, pine cones and wood apple shells were utilized as fillers along with areca sheath fibers in bio-based epoxy resin for fabricating a novel hybrid composite wherein the effect of these fillers in laminated composites has not been explored to a greater extent. The impact of reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
(81 reference statements)
1
1
0
Order By: Relevance
“…Shakuntala et al 28 have incorporated the wood apple shell in epoxy polymer and observed that it boosts the polymer composite's mechanical, erosive wear resistance, and visco‐elastic stiffness. A similar observation of the positive impact of fillers is found when wood apple filler hybridizes with a pine cone and is added to natural fiber 29 …”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Shakuntala et al 28 have incorporated the wood apple shell in epoxy polymer and observed that it boosts the polymer composite's mechanical, erosive wear resistance, and visco‐elastic stiffness. A similar observation of the positive impact of fillers is found when wood apple filler hybridizes with a pine cone and is added to natural fiber 29 …”
Section: Introductionsupporting
confidence: 64%
“…A similar observation of the positive impact of fillers is found when wood apple filler hybridizes with a pine cone and is added to natural fiber. 29 Although some research has been done in the past by taking WAD as filler in polymer composites, the sliding wear potential of the epoxy-WAD composites has not yet been explored. Further, majority of research to date has concentrated on the use of WAD as particulates filler in polymer composites, but no work has been done on FEM analysis of the sliding wear behavior of this polymer composite.…”
Section: Introductionmentioning
confidence: 99%
“…Various traditional thermoplastics such as polythene, polypropylene, acrylonitrilebutadiene-styrene copolymers, polyamide, polystyrene, poly(methyl methacrylate), poly(vinyl acetate), and polycarbonate were used as matrixes of polymer-wood composites [3][4][5][6][7][8][9][10]. These materials were also manufactured using thermosetting plastics like epoxy, polyurethane, and phenolic resin [11][12][13][14][15][16]. Fibre, wood chips, sawdust, and wood flour were used as fillers [3,4,8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Fibre, wood chips, sawdust, and wood flour were used as fillers [3,4,8,9,11]. The wood material came from both deciduous and coniferous trees [6,[15][16][17]. Fillers were used in their original form and after preliminary modification, which may include the removal of lignin, coating with magnetic particles, attachment of epoxy and methacrylate groups, and even modifications using ionising radiation [4,5,7,11,13,14].…”
Section: Introductionmentioning
confidence: 99%